Pengaruh Fasilitas Belajar di Era 4.0 Terhadap Hasil Belajar Siswa Kelas XI SMK Pasundan 1 Kota Serang - Kurniati Rahmadani; Desi Handrayani (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This study discusses the Effect of Learning Facilities on Student Learning Outcomes in Class XI at SMK Pasundan 1, Serang City. This study aims to determine the effect of learning facilities on student learning outcomes in class XI at SMK Pasundan 1 in Serang City. The sample for this research was 61 class XI students of Pasundan 1 Vocational School, Serang City, who acted as respondents. To answer questions from the formulation of the problem above, the type of research used is quantitative, while data collection techniques use questionnaires, observation, and documentation, and data analysis techniques use SPSS IBM 26. The research results of hypothesis testing use validity tests, reliability tests, normality tests, linearity tests, t-tests, and f-tests so that they show that learning facilities obtain a t-count of 8.257 > t-table 2.002 (sig 0.000 <0.05), meaning that H0 is rejected and Ha is accepted. Thus, it can be interpreted that there is an influence between learning facilities and student learning outcomes in class XI, SMK Pasundan 1 Serang CityRing Algebraic Structure, Prime Ideal Thinking Ability, Maximum Ideal.